Advances in the diagnosis and treatment of fungal infections of the CNS. Issue 4 (April 2018) - Schwartz, Stefan; Kontoyiannis, Dimitrios P; Harrison, Thomas; Ruhnke, Markus
Summary: Fungal infections of the CNS are challenging to treat and their optimal management requires knowledge of their epidemiology, host characteristics, diagnostic criteria, and therapeutic options. Aspergillus and Cryptococcus species predominate among fungal infections of the CNS. Most of these fungi are ubiquitous, but some have restricted geographical distribution. Fungal infections of the CNS usually originate from primary sites outside the CNS (eg, fungal pneumonia) or occur after inoculation (eg, invasive procedures). Most patients with these infections have immunodeficiencies, but immunocompetent individuals can also be infected through heavy exposure. The infecting fungi can be grouped into moulds, yeasts, and dimorphic fungi. Substantial progress has been made with new diagnostic approaches and the introduction of novel antifungal drugs, but fungal infections of the CNS are frequently lethal because of diagnostic delays, impaired drug penetration, resistance to antifungal treatments, and inadequate restoration of immune function. To improve outcomes, future research should advance diagnostic methods (eg, molecular detection and fungus identification), develop antifungal compounds with enhanced CNS-directed efficacy, and further investigate crucial host defence mechanisms.